Dimensi Pasar Modal Syariah - Mu'awwanah, Uliyatul; Ridho Illah, Ghoni Rizky; Lestari, Dian (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2023)
The Islamic capital market is a capital market whose activities are based on sharia principles. In the Islamic capital market, there is a dimension which explains the description contained in the Islamic capital market, both regarding the operational system on the Indonesian Stock Exchange and the regulations that apply to the capital market. There are differences in the Islamic capital market when compared to conventional capital markets. The difference can be seen in terms of the concepts applied to both. The Islamic capital market also provides an opportunity for investors to invest in accordance with Islamic principles. The focus of writing this article is as a means to provide knowledge for readers, especially for potential new investors so they can find out what is contained in the Islamic capital market. The method used in this writing is descriptive qualitative method using reference sources as a writing reference. The results or conclusions of this article are that understanding the aspects contained in the Islamic capital market can provide insight and knowledge for investors and the Islamic capital market can be an option for investors, especially Muslim investors, to invest in the Islamic capital market.